Prevalence of hypertension in adults in the Šumadija District, Serbia – A cross-sectional study - Marinković, Mirjana; Ilić, Nevenka; Djokić, Dragoljub; Andrejevic, Vesna; Damjanović, Gordana; Samardžić, Goran; Tufegdžić, Sanja; Vučic - Janković, Mila (Vojnosanitetski pregled, 2014)
Background/Aim. World Health Organization (WHO) studies on the global level have shown that one of the major problems of the public health is hypertension. Blood pressure level greater than 140/90 mmHg is directly and predictively linked to other cardiovascular diseases. The aim of this research was to determine the prevalence of hypertension and the risk groups among the adult population in the Šumadija District, Serbia. Methods. This cross-sectional study included 1.669 elderly population of the Šumadija District, aged 25–74. The study was performed according to the protocol of the Countrywide Integrated Noncommunicable Disease Intervention (CINDI) international program. Results. In the Šumadija District more than a half of the population aged 25–74 suffers from hypertension (53%). In the Šumadija District 9% of population has undiagnosed hypertension. In the group of people familiar with their high blood pressure problems, good disease control is achieved in only 46% of them. Statistically, hypertension occurs more frequently in males aged 45–74, of lower education, and in rural population. This is the target group for implementation of the high risk strategy. Statistically, there is a higher prevalence of hypertension in people suffering from myocardial infarction (p = 0.04), angina pectoris (p = 0.00), other cardiac diseases (cardiac insufficiency) (p = 0.00) and cerebrovascular crises (p = 0.04). Conclusion. A continuous increase of patients with hypertension, coupled with the developed complications and increase in cardiovascular diseases as a cause of death, points to the lack of effective access to prevention and early detection of these diseases in the primary health care among the risk groups in Šumadija.
Keywords: hypertension; serbia; prevalence; incidence; risk factors